2017 29th Chinese Control and Decision Conference (CCDC) 2017
DOI: 10.1109/ccdc.2017.7978394
|View full text |Cite
|
Sign up to set email alerts
|

An EEG-based brain-computer interface for gait training

Abstract: This work presents an electroencephalography (EEG)-based Brain-computer Interface (BCI) that decodes cerebral activities to control a lower-limb gait training exoskeleton. Motor imagery (MI) of flexion and extension of both legs was distinguished from the EEG correlates. We executed experiments with 5 able-bodied individuals under a realistic rehabilitation scenario. The Power Spectral Density (PSD) of the signals was extracted with sliding windows to train a linear discriminate analysis (LDA) classifier. An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
4
16
0
1
Order By: Relevance
“…It should be noted that the real-time accuracies reported in this study are taking into consideration every single prediction during the experiment (every single epoch is classified). Unfortunately, the current literature on real-time BCIs is somewhat disperse in the way the results are reported [ 26 , 30 , 33 , 34 , 35 , 36 , 37 ], but whenever it is possible to compare, our results coincide rather well with those of the literature. Our results are consistent with those of Zich et al [ 33 ] which have a real-time accuracy of 55–65%, [ 26 ] with around 65% accuracy (of first 30 sessions), and [ 30 ] with around 65% accuracy.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…It should be noted that the real-time accuracies reported in this study are taking into consideration every single prediction during the experiment (every single epoch is classified). Unfortunately, the current literature on real-time BCIs is somewhat disperse in the way the results are reported [ 26 , 30 , 33 , 34 , 35 , 36 , 37 ], but whenever it is possible to compare, our results coincide rather well with those of the literature. Our results are consistent with those of Zich et al [ 33 ] which have a real-time accuracy of 55–65%, [ 26 ] with around 65% accuracy (of first 30 sessions), and [ 30 ] with around 65% accuracy.…”
Section: Discussionsupporting
confidence: 80%
“…Unfortunately, the current literature on real-time BCIs is somewhat disperse in the way the results are reported [ 26 , 30 , 33 , 34 , 35 , 36 , 37 ], but whenever it is possible to compare, our results coincide rather well with those of the literature. Our results are consistent with those of Zich et al [ 33 ] which have a real-time accuracy of 55–65%, [ 26 ] with around 65% accuracy (of first 30 sessions), and [ 30 ] with around 65% accuracy. Meanwhile, Guger et al [ 34 ] reported the results of the best time point of the best session of each of their three subjects (98%, 93% and 87%), but a careful analysis of their data shows the average real-time classification accuracy is about 80%, 65% and 65% for their three subjects respectively.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations